Associations Between Parental SES and Children's Health-Related Quality of Life: The Role of Objective and Subjective Social Status. (15th November 2017) - Kim, Kay W; Wallander, Jan L; Peskin, Melissa; Cuccaro, Paula; Elliott, Marc N; Schuster, Mark A
Abstract: Objective: We examined (1) the relationship that parental objective social status (OSS) and subjective social status (SSS) have with children's health-related quality of life (HRQOL), (2) whether SSS mediates the association between OSS and HRQOL, and (3) whether these associations differ among Black, Latino, and White children. Method: Data came from 4, 824 Black, Latino, and White 5th graders in the Healthy Passages TM study. OSS was measured as parent educational attainment and net equivalent household income. SSS was measured by parent rating of community and national standing on the MacArthur Scale of Subjective Social Status. Child HRQOL was measured with child report on the Pediatric Quality of Life Inventory (PedsQL) physical and psychosocial scales. Structural equation modeling path analysis was conducted using Mplus version 7.4. Results: The data supported the hypothesized measurement and structural models. Whereas parental OSS was positively related to psychosocial HRQOL for all three racial/ethnic groups and to physical HRQOL for Latino children, parental SSS was not related to either for any of the racial/ethnic groups. Therefore, mediation by SSS was not supported for any group. Conclusion: OSS was confirmed to have stronger association with children's HRQOL than parental SSS. This is in contrast to some research on adults, raising the questions of how best to assess SSS relevant to children and at what point in development SSS may influence children's health and well-being. The persistent relationship found between parental OSS and child health suggests that efforts to improve low socioeconomic resources in families may contribute to improve children's health.